Stable isotope evidence for dietary and cultural change over the Holocene at the Sabana de Bogotá region, Northern South America - Delgado Burbano, Miguel Eduardo (2018)
The Sabana de Bogota in the northern Andes is an interesting region to investigate temporal patterns of dietary variation because it counts with a vast archeological and osteological record for the last 10,000 years. In this paper, stable isotope data of human archeological bone collagen and apatite were used to study the evolution of diet and major subsistence transformations taking place during the Holocene (∼9000–600 cal BP). Paleoenvironmental reconstructions and the isotopic ecology of the Sabana de Bogota were used as an interpretative baseline. Stable isotope measurements (δ¹3Ccol, δ¹3Cap, δ¹5N, and Δ¹3Ccol-ap) representing hunter-gatherers, horticulturalists, and agriculturalists (N = 134 individuals) were analyzed by using bivariate, regressional, and discriminant statistical techniques. Results show that early Holocene hunter-gatherers (9000–7000 cal BP) consumed mostly C3 vegetal resources locally available. In contrast, animal protein was less important. Middle Holocene hunter-gatherers (6000–4500 cal BP) continued with the food foraging pattern observed in the earlier counterparts and presented a slight increase in C₃ animal protein intake. During the initial late Holocene ca. 4000 cal BP, important shifts in subsistence strategies occurred when populations presented a trend toward mixed C₃/C₄ diets, and by ca. 3500 cal BP, there is a clear signal of C₄ crops (i.e., maize) consumption concomitant with the introduction of ceramic technology. During the final late Holocene (last 2000 cal years BP), intensive agriculture was adopted and humans presented relatively diverse diets integrated by C₄ and C₃ crops, C₃-C₄ feeding animals, and freshwater resources. Such dietary change coincides with an increase in sociopolitical complexity, population size, and a general decline in health.